Interrelationship of Tourism and Indigenous Knowledge, Skill, and Technology: A Study of Gurung, Magar, and Tharu (GMT) Homestays in Gandaki Province - Chaudhary, Anchala; Pokhrel, Shreedhar; Parajuli, Angana (Janaprakash Journal of Multidisciplinary Research, 2024)
Since this decade, tourism has become the world’s biggest industry in terms of people’s peaceful movement, income generation, and employment creation. The desires of Nepal are to focus on tourism due to its ‘low investment, high return’ attribute. Tourism, being a strong agent of change, transformation, promotion, and conservation of nature, culture, and the economy, is the priority sector of the central and provincial governments of Nepal. Tourism seems to be favored both people and state, mostly due to its economic derivatives. Its non-economic progenies are mostly obscure and latent. Therefore, this paper investigates and analyzes the interrelationships between tourism and indigenous knowledge, skills, and technology. Data from both primary sources and secondary literature was used to support the arguments. Qualitative methods were used to gather the information. Sixty-five semi-structured interviews were conducted: 25 with the Gurung community, 15 with the Magar community, and 25 with the Tharu homestay. The finding revealed that these ethnic communities used their peculiar indigenous knowledge, skills, and technology to entertain tourists in a home-friendly environment with their customs and traditions. Additionally, these communities helped revitalize their obsolete traditions while practicing homestay entrepreneurship.